Student Motivation for Academic Performance in Higher Education in Nepal - Devkota, Bhimsen; Giri, Surendra (Education and Development, 2020)
Motivation plays a key role in improving students’ learning outcomes. This study explored student motivation for better learning efforts and performance in examination in various campuses, which were classified as high, medium and low performing ones in connection with their academic performance. Students’ motivation was assessed in terms of their perception towards relevancy of the academic programme, motivation and commitment to complete the study, family environment and responsibility. Factors motivating students to attend the classes regularly were also examined. Utilizing a cross-sectional mixed-methods research design, 800 participants were selected to take part in the study from three ecological belts of Nepal. FGD and self-administered questionnaires were used as tools for data collection. Data were analyzed using SPSS 20.0. The results showed the students' commitment to complete the academic programme in time was weak as less than half (42.5%) of them were committed to completing their studies with excellent grades/marks. It was found that only a quarter of the students (26.6%) considered that the curriculum they studied was highly relevant; even a quarter of the students (24.4%) from high-performing campuses reported it—only one-fifth of them from high performing campuses expected to achieve A+ or distinction marks. The study environment in the family was found to be less enabling as only half of the students had separate study rooms at home. Students had to take responsibility for caring for their family members and children as well. Majority of students (68.4%)self-reported that they were always regular in the class, highest in low performing campuses (71.1%), followed by high performing (67.7%) and medium performing campuses (65.3%). By university, the population of students who were always regular was highest in KU (81.2%), followed by TU (68.5%), PU (62.9%) and PokU (61.1%). It has been suggested that the students should be provided with the opportunity for learning and earning environment and the curricula should be amended from time to time to make them employment oriented.